Management of Postoperative Discitis: A Study On 20 Cases of Prolapsed Lumber Intervertebral Disc (PLID) Operation In A Tertiary Level Hospital in Bangladesh - Das, Sukriti; Mahmood, Ehsan; Alam, Md Jahangir; Rashid, Md Mamunur; Mitra, Pijush Kumar (Journal of Dhaka Medical College, 2015)
Context: The incidence of postoperative discitis is relatively uncommon. The paucity of physical examination findings with a high index of suspicion in any patient presenting with increasing back pain after prolapsed lumber intervertebral disc (PLID) operation gives clue of diagnosis. Purpose: To see the incidence, pathophysiology, laboratory markers and imaging finding of postoperative discitis, at the same time recommendation on treatment strategies with long term clinical outcome of discitis patient in Dhaka Medical College Hospital (DMCH), a tertiary level hospital in Dhaka, Bangladesh. Methods: In this observational study, 20 patients were recruited who underwent PLID operation in the Department of Neurosurgery, DMCH, Dhaka, from January 2012 to June 2014. After preliminary selection of patients a specific protocol was followed, by taking history, clinical examination, biochemical parameters and neuroimaging. Result of treatment was observed on the basis of symptomatic improvement, with laboratory and imaging findings. Results: The most common etiological agent is staphylococcus aureus. The C-reactive protein is the most sensitive clinical laboratory marker to assess the presence of infection and effectiveness of treatment response. MRI is the imaging modality of choice in the diagnosis of discitis (100%). The majority of patients are managed adequately with culture specific antibiotics and immobilization with good long term outcomes (75%). Operative intervention in those patients who fails to respond to medical treatment (25%). Conclusion: Postoperative discitis is a rare complication after PLID operation. Its diagnosis needs high index of suspicion, appropriate laboratory and imaging studies helps in diagnosis. In the majority of patients antibiotics and spinal immobilization has been shown to produce good long term outcomes. Operative intervention is rarely necessary in patients failing conservative treatment. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 186-190